UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIF SMP N2 SEMARANG MELALUI PENERAPAN PENGAJUAN MASALAH PADA MATERI BANGUN DATAR TAHUN PELAJARAN 2010/2011 - Suroto Suroto (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2011)
One of the problems in learning mathematics at school is the low ability of students in solving story problems associated with daily life, so that the results achieved are not optimal.?é?áThis is due to one of them is the ability of students in solving problems.?é?áTo overcome, it required an appropriate learning, one of which is to use the application filing problem as a solving problem. The purpose of this study is to improve the learning outcomes of Math class grade VII F at SMP N2 Semarang on solving word problems related to flat wake.?é?áAs matter of that, the KKM used today is 77, therefore learning strategies to improve learning outcomes is steadily promoted. Problem in this study is whether the filing of the problem of learning can improve learning outcomes on completion of word problems relating to wake up flat??é?áThe method used is two conducted submission cycles and each cycle consist of two meetings.?é?áEach cycle comprises four phases: planning, action, observation and reflection.?é?áStudents discuss with the group in accordance with one specified group comprising 4 to 5 students. From the research results obtained by the average value in the first cycle is 80.5 and 73.1% completing the study. Hence, it does not meet the completeness limit of learning because learning is said complete if 85% achieves the exhaustiveness learning.?é?áThis is due to the role of teachers in learning still dominates the classroom so that students tend to be less active.?é?áIn the second cycle after extensive reflection and change in learning is getting satisfactory results.?é?áAlmost all students are actively involved in discussions so that the average value of learning to 87 and 88.5% completeness. Based on the results of these studies, the learning is very effective by filing problems to improve students' mathematics learning outcomes at of grade seven in VIIF in the case of ?é?áSMP N 2 Semarang on a flat wake of the academic year 2010/2011. Key Words: Ability to Think Creatively, Filing Problems, Learning Outcomes, Learning Completed, Koopertif.